Progress in Managing Heart Failure: an in-depth Review of Sacubitril/Valsartan Combination Therapy - Neeraj Hiremath; Jayasheela S. Hiremath; Sanatkumar B. Nyamagoud; Agadi Hiremath Viswanatha Swamy (MGM Journal of Medical Sciences)
Heart failure is a severe cardiovascular condition when the heart fails to adequately pump blood or oxygen to support the body’s organs. Sacubitril/valsartan, an emerging angiotensin receptor-neprilysin inhibitor (ARNI) known for its superior efficacy to conventional treatments, has revolutionized the management of heart failure. The United States Food and Drug Administration has approved the drug’s use in treating patients with chronic heart failure with reduced ejection fraction (HFrEF). Clinical trials have demonstrated its effectiveness in reducing hospitalizations and mortality rates associated with heart failure across various patient populations, including those with low ejection fraction. Numerous significant clinical trials have investigated the drug’s safety and efficacy in treating individuals with heart failure and a failing systemic right ventricle. This review delves into the current landscape of cardiovascular medicine, the role of pharmacology, and the safety profile of this medication.